Pengaruh Modal, Tenaga Kerja dan Luas Lahan terhadap Jumlah Produksi Kopi Arabika di Kecamatan Kintamani Kabupaten Bangli - Utami Dewi, Ida Ayu Nyoman; Yuliarmi, Ni Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 6, Juni 2017 (pp. 920 - 1156), 2017)
Indonesia is an agricultural country which most of the population works in agriculture sector. Therefore, the agricultural sector contributes significantly to economic growth. Agricultural sectors is expected to fulfil the needs of people consumption.This research have a purposes are: (1) to determine the effect of capital, labor, and land simultaneously and partially on the number of Arabica coffee production in the district of Kintamani Bangli, (2) to determine the nature of Arabica coffee production in the district of Kintamani Bangli. The samples of this study are 100 farmers of arabican coffee that taken by using the proportional area random sampling method , which is sampling based on the region where the respective parts of the sample drawn at random. This study uses primary data, that means data is collected by interviews. Data analysis techniques in this research is multiple linear analysis techniques. The result of this study are, capital, labor, and land simultaneously significant effect against the number of Arabican coffee production in Kintamani Bangli. Partially, capital, labor and land area are significantly influence the amount of Arabica coffee production in Kintamani Bangli.
Keywords: Jumlah Produksi, Modal, Tenaga Kerja, Luas Laha